A prática das investigações internas no Brasil e a aplicabilidade do direito à não autoincriminação - Forsman, Ana Gabriela da Costa Carvalho (2022)
Although Brazil has no clear regulation or robust case law on internal investigations, they have increased and taken relevance both by private and state-owned companies. This paper is based on field research (i.e., interviews with expert attorneys and members of the Federal Prosecutors’ Office, Comptroller General’s Office and Brazilian Antitrust authority), foreign and Brazilian legislation, doctrine and case law and aims to: (i) describe how internal investigations have been carried out in Brazil (e.g., procedures adopted and how local courts and public officials have been handling related issues); (ii) assess whether the privilege against self-incrimination (i.e., nemo tenetur se detegere) applies to internal investigations involving alleged criminal misconduct as well as its effect; and (iii) recommend best practices. This paper seeks to be of use to law practitioners by clarifying gaps and providing legal certainty on the topic. In addition, this paper analyzes various theories regarding the enforceability of the right against selfincrimination within internal investigation and concludes that such right is enforceable when private and state action are present and entwined. At last, this paper proposes to solve practical cases and recommends best practices (e.g., regarding the duty to inform interviewees of their right to silence and public authorities’ approach during settlement negotiations towards the methodology applied in the gathering of evidence under internal investigations).